POLA KEPEKAAN KUMAN TERHADAP ANTIBIOTIKA DI RUANG RAWAT INAP ANAK RUMAH SAKIT KANKER DHARMAIS JAKARTA TAHUN 2014 - Mega Mirawati; Estu Lestari; Demak L Tobing (Poltekkes Kemenkes Jakarta III, 2015)
Antibiotic resistance is becoming a public health threat in Indonesia, then to controlgerms that are immune surveillance is needed periodically. Patterns germs andsensitivity test results can be used as the basis for empirical antibiotic. This studyaims to determine the sensitivity pattern of bacteria to antibiotics in inpatient childrenDharmais Cancer Hospital Jakarta in 2014. This study is a descriptive study usingsecondary data sensitivity test results of bacteria to antibiotics in inpatient childrenDharmais Cancer Hospital in 2014. Results culture showed that the type of pathogensfound in January-June 2014 was Pseudomonas aeruginosa (14.99%), Esherichia coli(13.89%), and in July - December 2014 pathogenic germs found were Acinetobacterbaumannii (16, 25%) and Escherichia coli (15.35%). Of the 990 isolates obtainedsensitivity pattern of germs showed the sensitivity of Gram positive to ceftazidime(100%), Trimethoprim (100%), Linezolid (100%), Cefuroxime (100%), Amikacin(100%), Netilmicin (100%), Vancomycin (100%) and Tigercycline (100%). Gramnegativebacteria highest sensitivity towards Doripenem. Gram-positive bacteriahighest resistance to ampicillin (100%) and Moxifloxacin (100%). Gram-negativegerms showed the highest resistance to Amoxicillin results (100%). The conclusionthat the Gram-positive bacteria are sensitive to ceftazidime, Trimethoprime,Linezolid, Cefuroxime, Amikacin, Netilmicin, Vancomycin and Tigercycline andGram-negative bacteria sensitive to Doripenem.